2005
DOI: 10.1002/dvdy.20511
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal regulation and cleavage by matrix metalloproteinase stromelysin‐3 implicate a role for laminin receptor in intestinal remodeling during Xenopus laevis metamorphosis

Abstract: The 37-kd laminin receptor precursor (LR) was first identified as a 67-kd protein that binds laminin with high affinity. We have recently isolated the Xenopus laevis LR as an in vitro substrate of matrix metalloproteinase stromelysin-3 (ST3), which is highly upregulated during intestinal metamorphosis in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…ST3 may accomplish this in part through direct/indirect remodeling of the ECM. In addition, the 67-kDa receptor for laminin (LR), a major ECM component of the basal lamina, was recently identified as a substrate of ST3 using a yeast twohybrid screen (Amano et al, 2005a) and is cleaved by ST3 in metamorphosing tadpole intestine (Amano et al, 2005b). Thus, another possible mechanism of ST3 function could be that TH induces fibroblasts to express ST3, which in turn cleaves LR and alters epithelial cell-ECM interactions.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…ST3 may accomplish this in part through direct/indirect remodeling of the ECM. In addition, the 67-kDa receptor for laminin (LR), a major ECM component of the basal lamina, was recently identified as a substrate of ST3 using a yeast twohybrid screen (Amano et al, 2005a) and is cleaved by ST3 in metamorphosing tadpole intestine (Amano et al, 2005b). Thus, another possible mechanism of ST3 function could be that TH induces fibroblasts to express ST3, which in turn cleaves LR and alters epithelial cell-ECM interactions.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…In particular, we have shown that LR is a conserved substrate of ST3 and is cleaved by ST3 in the remodeling intestine during metamorphosis (47,48). Spatiotemporal expression of LR and its cleavage suggest that LR cleavage by ST3 plays a role in T3-induced larval epithelial cell death in the remodeling intestine during metamorphosis (48 (Fig.…”
Section: Transgenic Expression Of St3 Induces Apoptosis Predominantlymentioning
confidence: 72%
“…Although ST3 may cleave ECM proteins strongly in the in vivo environment, these findings suggest that the cleavage of non-ECM proteins is likely important for its biological roles. Consistently, we have recently identified a cell surface receptor, laminin receptor (LR) as an in vivo substrate of ST3 in the tadpole intestine during metamorphosis (47)(48)(49). Analyses of LR expression and cleavage suggest that LR cleavage by ST3 is likely an important mechanism by which ST3 regulates the interaction between the larval epithelial cells and the ECM to induce cell death during intestinal remodeling (47,48).…”
mentioning
confidence: 64%
See 2 more Smart Citations